APPLICATION OF PILATES MEANS FOR ALL-ROUND PHYSICAL DEVELOPMENT OF FEMALE CANOEISTS AGED 12-13 (Sport Science Research, 2025)
The article describes the reasons for seeking additional means of physical education that, against the background of the limited volume and intensity of physical exertion on the bodies of female canoeists aged 12-13, can lead to adaptive shifts. The use of Pilates techniques in physical training is suggested as one such means. The technique includes a set of progressively more complex exercises from the Pilates system aimed at developing flexibility and strengthening the muscles of the arms, neck, and sides of the back; improving the spine and correcting posture; stretching the spine and strengthening the back from the upper spine to the coccyx; working the lumbar muscles, buttocks, and thigh biceps; exercising the muscles of the back and abdomen together; developing strength and endurance in the back muscles; and improving flexibility, balance, and coordination. The developed method of incorporating Pilates tools into physical training is recommended for enhancing the functional and physical fitness of female canoeists aged 12-13 years.
Keywords: physical fitness, pilates, canoe athletes, flexibility, speed, coordination abilities, endurance